The Impact of Notches on the Fracture Strength of Complete Upper Dentures: A Novel Biomechanical Approach - Anthony, Prombonas; Poulis, Nikolas A.; Yannikakis, Stavros A. (European Scientific Journal, ESJ, 2019)
This paper focuses on introducing a new biomechanical method for estimating the fracture strength of complete upper dentures (CUDs) and evaluating which notch mode has the greatest impact on their strength reduction. Forty identical CUDs were constructed according to a previously applied methodology, and it was divided into four groups of ten specimens. This is dependent on the location and size of the notches in the labial region of the denture. The upper grip of a universal testing machine was replaced by a newly designed and constructed loading element for simulating the intraoral denture loading conditions. The fracture load and the deflection at fracture were measured, while the fracture energy was calculated (product of the load to the deflection) under compression. The measurement of fracture energy through the present novel method leads to more precise outcomes. The highest impact on the reduction of CUDs strength was for the combination group 4 with both the midline (incisal) diastema and deepened labial fraenal notch. Nevertheless, it gradually reduced for group 2 with midline (incisal) diastema, group 3 with deep labial fraenal notch, and group 1 with initial-shallow labial fraenal notch (P<0.001). The conditions for groups 2 and 4 strongly require reinforcement of the denture bases.